'AN EFFECTIVE ENRTY STRATEGY TO ENTER INTO INDIAN AUTOMOBILE MARKET’ - Patil, Gaurank (2013)
The world economy has observed tremendous changes in way businesses are expanding globally in the last three decades and ‘Foreign Direct Investment’ is the main reason behind this change. Multinational companies looks upon FDI as a major catalyst to fulfill their financial, technical, employment generation and competitive efficiency requirements. The highly developing South Asian country, India, has attracted an ample number of multinational companies from various countries. In FY2012 - 13, the country has attracted FDI of around US$46.8b from various sectors, in which Automobile industry contributes the third largest share after service industry and telecommunication. It is expected that India will be among the top five auto-producers in the world by 2015 because of various factors, like increasing incomes, growing the middle class and young population, greater availability of credit and financial options and strong demand growth.